The Language Acquisition of a Child With Mental Retardation (a Psycholinguistic Study) - Octaria Putri Nurharyani; Bivit Anggoro Prasetyo Nugroho (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
This research aims at describing the language acquisition or the ability to acquire language of a child with mental retardation. The data of this study is the language acquisition of Herman (a 2-year-old-child). Data sources were categorized into two groups; the primary data was obtained from Herman’s utterances, and the secondary data was from literature sources (books about psycholinguistics). This research used descriptive qualitative method. Data were collected, clarified, and analyzed according to the established criteria. The result of the study indicated that there was a delay in the language acquisition of the child with mental retardation, yet the process was in a good development.